Priority technologies and innovations in the fishing agribusiness by the year 2032. Foresight study through the Delphi method (2017)
Introduction. This paper is presented in the framework of the project "Alternatives for the use of by-products derived from fishing agribusiness", Universidad del Cauca, through the research group: Harvesting of Byproducts and Agro-industrial Residues, ASUBAGROIN, which aims at the development and implementation of technologies and innovations for the use of by-products generated by the fishery activity, in order to improve research and innovation capacities in that specific subsector. Objective. The purpose of this paper is to prioritize innovations in fish by-products by consulting experts to identify innovation, technology and knowledge management activities for the institutions involved in the sector. Materials and methods. The methodology consisted in the application of the Delphi method through a structured and anonymous survey with national and international experts on topics related to the fish farming industry, using a questionnaire of 143 items divided in five groups, in order to choose priority Articulo original / Original article / Artigo original DOI: 10.22507/rli.v14n2a10 topics. Results. The questionnaires were filled out by 37 experts from Colombia, Brazil, the United States, Mexico and Uruguay; a total of 54 priority themes were obtained, corresponding to 38% of the topics presented. Among the topics of greatest consensus and mode are the formulation of concentrated foods, partial substitution of fishmeal, extrusion of concentrated foods, Omega-3 rich oil, probiotics, bioaccumulation, microalgae of fish processing wastewater, technological appropriation, technological evaluation, measurement of intellectual capital, innovation processes, and technological strategies. Conclusions. One of the main contributions of the study is the benefit for current players in the fish innovation system and new ones, such as technology development centers and new ventures, since they will have a route map of innovations on which to focus their investments and project initiatives.